Inherit more - Shenkman, Martin M. (John Wiley & Sons, 2003)
Elderly parents and benefactors need your help, and helping them can also preserve the largest financial windfall of your life–an inheritance. Finally, there’s a book that answers all your questions. Inherit More is the straightforward, practical guide to keeping more of what’s rightfully yours. It also helps you broach a difficult subject with your loved ones. It provides sensitive advice on talking to parents and practical guidance for dealing with family, financial, and other issues critical to every benefactor and critical to preserving your inheritance.